Detection of Organic Free Radicals in Coal-dust Exposed Lung Tissue and Correlations with Their Histopathological Parameters - B. Jafari; N. S. Dalal; V. Vallyathan; F. Y. H. Green (The National Institute for Occupational Safety and Health (NIOSH), 1989)
"Using electron spin resonance (ESR) spectroscopy we have carried out a systematic study of the measurement of concentrations of organic free radicals in freeze-dried lung tissue. Sixty-six tissue samples were obtained from the National Coal Workers' Autopsy Study (NCWAS). The samples were characterized in terms of the concentration per gram of the free radicals, and examined in relationship to the histopathological parameters such as age, numbers of years in the mining atmosphere, the degree of disease, and smoking history. Preliminary results indicate a positive correlation between the free radicals in the lung tissue and the severity of pneumoconiosis.IntroductionThis paper summarizes our electron spin resonance (ESR) measurements of the concentration of organic free radicals in the freeze-dried lung tissue of autopsied coal miners. This work was undertaken because it is well known that most coals contain carbon-centered organic free radi¬cals,(1,2) and recent studies from our laboratories indicated that reactive free radicals might play a role in the biochemi¬cal mechanism of coal workers' pneumoconiosis (CWP) (3) Thus we obtained 144 lung-tissue samples from the Nation¬al Institute for Occupational Safety and Health (NIOSH) in Morgantown. The samples came from the data bank of the National Coal Workers' Autopsy Study (NCWAS). This selection was unique because fairly detailed histopathologi¬cal information was available for each sample.Other recent studies in this field are those of Ohta et al (4) who conducted ESR measurements on black dust deposited in autopsied human lungs, but no coal miner was included therein. Earlier Retcofsky (2) had examined one lung-tissue sample via ESR spectroscopy and had concluded that the free radicals in the lung tissue reflected simply the fusain (narrow component) ESR signals. The present study was thus undertaken to complement the earlier work (2-4) and the results indicate a positive correlation with the disease severity fairly strongly."